Analisis Metode Fuzzy Analytical Network Process untuk Sistem Pengambilan Keputusan Pemeliharaan Jalan - Rizky Ardiansyah; M. Aziz Muslim; Rini Nur Hasanah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Road, as one of the land transportation infrastructure, is important for economic improvement of an area. It needs special and regular maintenance by the local government, in order to keep the road in good condition. For this purpose, the government conducts a survey with the aim of getting criteria for determining priority of road maintenance. The obstacle in implementation of road maintenance is the lack of criterias which make difficulties in determining the priority of road maintenance. Decision-making system is needed to solve the problems of determining the priority of road maintenance. Fuzzy Analytical Network Process (FANP) can solve the problem by calculating the criteria to get priority value. This method consists of many steps, namely weighting among criteria, weighting among sub-criteria, triangular fuzzy number, fuzzy synthesis, weight matrix, and priorities. The results show that the priority order of routine road maintenance is Jl. Jakarta, Jl. Kelud, and Jl. Kyai Tamin. The accuracy rate obtained in this research is 66.67%. Sensitivity test shows that the damage of the roads and the road density are important factors in generating the weight value road maintenance priorities.